Development of a business continuity plan and implementation of headquarters operation training considering a nuclear disaster - Tsujiguchi, Takakiyo; Naraoka, Masato; Yamanouchi, Kanako; Mori, Ryutaro; Maekawa, Ryusei; Kashiwakura, Ikuo; Ito, Katsuhiro (Frontiers in Public Health, 2025)
Hospitals play a critical role in protecting the lives and health of residents during disasters, making the development and effective implementation of business continuity plans (BCPs) essential. During nuclear disasters, it is particularly important to establish a system capable of specialized responses. This study reports on the efforts of our hospital, designated as an Advanced Radiation Emergency Medical Support Center, to develop a BCP that addresses both natural and nuclear disasters and implement operation training at the headquarters. In 2022, nuclear disaster response was incorporated into the existing BCP, and in 2023, training exercises were conducted based on compound disaster scenarios. During the training, participants practiced information sharing and decision-making through simulated communication while performing their designated roles. The post-training review identified issues such as a limited understanding of nuclear disaster-specific terminology, a lack of established procedures for dispatching radiological technologists, and an absence of media response guidelines. These findings demonstrated the practical value of BCP development and training implementation for enhancing preparedness against various types of disasters, and provide insights for the continuous improvement of hospital disaster response systems and educational frameworks.